Upaya optimalisasi infiltrasi menuju tata guna lahan berkelanjutan - Sahabuddin Latif; Nurhikmah Paddiyatu; Andi Yusri; Sumarni Baking (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The degradation of land due to conversion is a global process with a significant effect on land use. The intensification of land use in Makassar City is observed to have dramatically affected water retention hydrology, thereby, leading to an increase in volume, runoff rate, and filtration loss. Therefore, it is necessary to optimize infiltration by mapping the classification of infiltration capability based on the land-use changes observed between 2005 and 2020 as well as the inundation occurring due to surface runoff. This research uses a quantitative method by calculating the run-off spatial data and statistics to determine the area with low infiltration capability in the built-up environment. The results showed a decrease in infiltration capability of 3.6% which represents 617.72 ha at critical levels in the built-up area in the last 15 years. This means it is possible for decision-makers to implement infiltration optimization steps as the alternative solution by focusing only on the land-use distribution with critical initial conditions. The findings of this research are expected to minimize surface runoff rate and excess inundation potential in order to achieve sustainable land use in Makassar City.